Parallel coupled bandpass filter for WiMAX applications / Abdullah Tohir Abdul Aziz - Abdul Aziz, Abdullah Tohir (2010)
The work concentrates on the design of a parallel coupled bandpass filter (PCBPF) for WiMAX application. The design is a third order filter developed at the centre frequency of 5.77 GHz. The bandwidth of the filter is 9%. The filter is implemented by using epoxy laminate with relative permittivity, er=3.0 with substrate thickness of 0.75mm. Simulations are proposed throughout the work to illustrate the various possibilities offered by the concept by using the Agilent Genesys 2009 software. Experimental results in microstrip technology are also presented in order to validate the idea.